The impact of eco-tourism on land-use patterns: The case of Dinokeng eco-tourism pilot project in Gauteng Province - Machethe, Charles Lepepeule (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Rural Development Planning))--University of Pretoria, 2006.